Athenry Castle, south interior wall of hall, window hood - O'Donovan, Danielle (My University, 2008)
Hood of window angle shaft. Moulding comprises: angle keel flanked at either side by quarter hollows and chamfers.
Window
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Medieval; keel moldings